Pengembangan Media Pembelajaran Berbasis Website (WORDWALL) Mata Pelajaran Fiqih Kelas VII Di Madrasah Tsanawiyah Muhammadiyah 12 Palirangan Untuk Meningkatkan Hasil Belajar Siswa - Idzi’ Layyinnati (STIT Muhammadiyah Paciran Lamongan, 2022)
This research has purpose to produces learning materials that proper theoritically and empirically feasible digital learning media in the form of a website (wordwal) supported by increased learning outcomes and student responses to learning with the object of student research in MTs. This study uses a 4D development model (four D models) define, design, develop and disseminate but do not disseminate with a trial design using a one group pretest posttest design implementation. Collecting data using validation methods, questionnaires, tests and observations while data analysis is descriptive qualitative. The results of the study are: Variables related to the validity of the website (wordwal) in terms of feasibility in the theoretical and empirical fields, respectively 82.5% and 91.3 and very positive student responses 80.3%; assessment of student learning outcomes increased from N-Gain 0.86 with the high category. The media developed is suitable for use in learning and can improve student learning outcomes.